Nicotine chewing gum in general practice: effect of follow up appointments. Issue 6479 (11th May 1985) - Marshall, A; Raw, M
Abstract : Two hundred smokers who were judged by their general practitioner to be motivated to stop smoking were allocated to one of two groups. All were offered an initial appointment at which they were advised to stop smoking and offered nicotine gum. One group then received no further appointments. The other was offered four further appointments over three months. Both groups were followed up at six and 12 months. At one year follow up 15.5% overall had stopped smoking, 14% in the low and 17% in the high contact group. This is better than most results so far reported for nicotine chewing gum in general practice, suggesting that general practitioners can use it to good effect. We compare this result with others achieved in general practice.